2008
DOI: 10.1177/0192623308322016
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Cross-species Measurement of Cardiac Troponin-I Using the Erenna Immunoassay System

Abstract: Serum cardiac troponin-I (cTnI) has been validated as a biomarker for cardiotoxicity in numerous animal models; however, owing to sensitivity issues cTnI concentrations in healthy, resting animals used in toxicology studies have not been established. Serum from healthy and isoproterenol hydrochloride (iso)-treated rats, dogs, and monkeys were assayed using the Erenna system. The Erenna cTnI assay provided sensitivity < 1 ng/L across human, rat, dog, and monkey cTnI. Linear responses (R 2 = 0.99) were observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 19 publications
2
50
2
Order By: Relevance
“…Second, the ULoQ should be adequate to quantify large relative increases of cTnI concentration above baseline in studies of cardiotoxic compounds in rats. For example, cTnI concentrations in rats have been reported to be well over 1000 pg/mL following administration of isoproterenol at doses 0.5 mg/kg (Mitra et al 2008;Schultze et al 2008;York et al 2007), which is significantly greater than a fivefold change from our observed reference range. Thus, to provide maximum coverage of all possible and expected cTnI concentrations, such longitudinal studies require a sensitive immunoassay (LLoQ of at least 3 pg/mL) coupled with a wide dynamic range of over four logs.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Second, the ULoQ should be adequate to quantify large relative increases of cTnI concentration above baseline in studies of cardiotoxic compounds in rats. For example, cTnI concentrations in rats have been reported to be well over 1000 pg/mL following administration of isoproterenol at doses 0.5 mg/kg (Mitra et al 2008;Schultze et al 2008;York et al 2007), which is significantly greater than a fivefold change from our observed reference range. Thus, to provide maximum coverage of all possible and expected cTnI concentrations, such longitudinal studies require a sensitive immunoassay (LLoQ of at least 3 pg/mL) coupled with a wide dynamic range of over four logs.…”
Section: Discussionmentioning
confidence: 44%
“…All sera and calibrators were tested in duplicate and the results are presented as the mean of the two measurements. The human National Institute for Standards and Technology standard was used as the standard reference for calibration, which has been shown previously to provide accurate determinations of cTnI concentration in rat serum with this assay (Schultze et al 2008). …”
Section: Sample Analysismentioning
confidence: 99%
“…While our assessment of the research assay was limited and the samples were over 2 years old, the precision of the assay was notably not as high as has been reported for rat serum with another high-sensitivity cTnI assay (Schultze et al 2008). Overall, it has been shown that cTnT is stable frozen for a least a year with a minimal decrease (7%) after 2 years of storage (Basit et al 2007).…”
Section: Discussionmentioning
confidence: 78%
“…cTnI concentrations in healthy human individuals, rats, dogs and monkeys are in the picomolar range, well below the analytical sensitivity of commercially available assays. 22,23 It is highly probable that healthy horses have similar plasma cTnI concentrations and assay sensitivity limitations are the likely reason for failure to detect cTnI in many horses. In addition to undetectable cTnI concentrations pre-anesthesia, most horses of this study did not develop detectable cTnI following anesthesia.…”
Section: Discussionmentioning
confidence: 99%